O uso habitacional e as estratégias de revitalização do bairro do Recife (PE) a partir da década de 1990 - Carvalho, Ana Paula Buarque de (2019)
Since the 1990s, the old 'Bairro do Recife', (city of Recife/Brazil) has undergone a revitalization process. It began with the elaboration of the "Bairro do Recife Revitalization Plan" and, gradually, it was reinforced by the implantation of four intervention projects (Polos Bom Jesus, Alfândega, Arrecifes and Pilar) and then, the installation of Porto Digital, one of the largest Technology Parks in the country, which had a big role in improving the dynamic of the local economy. The 'Bairro do Recife', in turn, has become an important postcard of the city, fomenting several cultural and leisure events. However, the residential use, which was foreseen in the beginning of this process and is usually considered essential to revitalize historical areas, was never stimulated by those projects. Therefore, the main goal of this research is to understand the reason for the lack of concern about residential use, explaining what limits or inhibits this type of land use in the 'Bairro do Recife', once it was provided with a large sum of investments – even more if we consider other neighborhoods of the Historic Center of the city. From a large survey of several kinds of documents concerning the interventions in the 'Bairro do Recife' (implemented or not) and from interviews with former and current public managers of the City Hall, it was attempted to identify if the residential use was considered in discussions and if there was any correlation between the interventions that were executed and the abandonment of this kind of land use. Our research pointed to the low interest of the public power in stimulating this use in the neighborhood, besides demonstrating the relevance of Porto Digital for the revitalization, which, while ensuring greater recovery and preservation of the properties, induced its use by economic activities that meet their demands. The research also points to the resumption of real estate market investments in residential real estate in the central neighborhoods, where Recife has a disadvantage in attracting these investments, as it has greater legal restrictions to protect its assets.